2018
DOI: 10.1038/s41598-018-25384-x
|View full text |Cite
|
Sign up to set email alerts
|

Pathological conversion of regulatory T cells is associated with loss of allotolerance

Abstract: CD4+CD25+Foxp3+ Regulatory T cells (Tregs) play a critical role in immune tolerance. The plasticity and functional adaptability of Tregs in an inflammatory microenvironment has been demonstrated in autoimmunity. Here, using a double transgenic mouse model that permits Foxp3 lineage tracing, we investigated the phenotypic plasticity of Foxp3+ Tregs in a well-characterized murine model of corneal transplantation. In order to subvert the normal immune privilege of the cornea and foster an inflammatory milieu, hos… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
77
0
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 82 publications
(79 citation statements)
references
References 56 publications
1
77
0
1
Order By: Relevance
“…However, systemic administration of immunosuppressive agents—such as rapamycin—cause patients to develop susceptibility to infection because these drugs also suppress healthy immune function needed to combat pathogens. One approach to prevent susceptibility to infection is by targeting the delivery of immunosuppressive drugs to activated T cells in proximity to the transplanted organ . Using hydrogels to reengineer the environment around the transplant site provides a means to probe how this local change alters the activity of graft‐reactive T cells.…”
Section: Biomaterials Enable Studies At the Interface Of Immune Cellsmentioning
confidence: 99%
“…However, systemic administration of immunosuppressive agents—such as rapamycin—cause patients to develop susceptibility to infection because these drugs also suppress healthy immune function needed to combat pathogens. One approach to prevent susceptibility to infection is by targeting the delivery of immunosuppressive drugs to activated T cells in proximity to the transplanted organ . Using hydrogels to reengineer the environment around the transplant site provides a means to probe how this local change alters the activity of graft‐reactive T cells.…”
Section: Biomaterials Enable Studies At the Interface Of Immune Cellsmentioning
confidence: 99%
“…In reverse, Treg cells can alter their phenotype and functions to adopt a Th17‐like effector cell profile too. It is important to understand these alterations as they can impact the regulatory balance in the graft . A further limitation is that much of our understanding to date originates from in vitro experiments and in vivo murine (or non‐human primate; NHP or swine) models .…”
Section: Introductionmentioning
confidence: 99%
“…9,10 Substantial progress has been made in determining the mechanisms by which host factors, such as recipient bed vascularity and inflammation, influence the immune response to corneal allografts. 16 Studies performed by our laboratory [17][18][19][20][21][22][23][24] and others [25][26][27] indicate the critical contribution of Foxp3 + Tregs to immune tolerance in the setting of corneal transplantation. 16 Studies performed by our laboratory [17][18][19][20][21][22][23][24] and others [25][26][27] indicate the critical contribution of Foxp3 + Tregs to immune tolerance in the setting of corneal transplantation.…”
Section: Introductionmentioning
confidence: 99%
“…17,[28][29][30] In the setting of corneal transplantation, we have demonstrated that Tregs derived from mice with inflamed and vascularized host beds that are prone to quick rejection (ie, high-risk hosts) have decreased expression of Foxp3 (the transcription factor that is crucial for their development and function) relative to low-risk hosts that survive long term. 17,[28][29][30] In the setting of corneal transplantation, we have demonstrated that Tregs derived from mice with inflamed and vascularized host beds that are prone to quick rejection (ie, high-risk hosts) have decreased expression of Foxp3 (the transcription factor that is crucial for their development and function) relative to low-risk hosts that survive long term.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation